CAUSALITY OF REGIONAL ORIGINAL INCOME (PAD), REGIONAL EXPENDITURE, POVERTY LEVEL AND ECONOMIC BENEFICTS - Ulfa, Nadia; Farma, Junia; Ariani, Puji (Universitas Syiah Kuala, 2024)
This study aims to determine the correlation between Regional Original Income (PAD), regional expenditures, poverty and economic benefits as measured by the level of the Human Development Index (IPM). This data research uses panel data from 23 districts/cities in Aceh in the period 2014-2019. Panel Vector Error Correction Model (PVECM) and panel Granger causality test were used to analyze the data. This study shows that there is a long-term relationship between variables, namely regional spending, poverty, and Human Development Index (IPM). Whereas in the shortterm PAD has no effect on poverty, but PAD does not affect regional spending and has a negative effect on HDI, then regional expenditure is not affected by poverty, but does not have a positive effect on HDI, while it has a negative impact on HDI. The results of the Granger Panel causality test can be found that there is a causal relationship between regional spending and HDI on PAD, while the disease has a one-way relationship with PAD. Then there is also a one-way relationship between regional spending and poverty on HDI, but poverty and HDI have no relationship between the two.